Integration of Umbilical Cord Mesenchymal Stem Cell Application in Hydroxyapatite-Based Scaffolds in the Treatment of Vertebral Bone Defect due to Spondylitis Tuberculosis: A Translational Study - Ahmad Jabir Rahyussalim; Ahmad Nugroho; Muhammad Luqman Labib Zufar; Irfan Fathurrahman; Tri Kurniawati (Stem Cells International)
Background. Vertebral bone defect represents one of the most commonly found skeletal problems in the spine. Progressive increase of vertebral involvement of skeletal tuberculosis (TB) is reported as the main cause, especially in developed countries. Conventional spinal fusion using bone graft has been associated with donor-site morbidity and complications. We reported the utilization of umbilical cord mesenchymal stem cells (UC-MSCs) combined with hydroxyapatite (HA) based scaffolds in treating vertebral bone defect due to spondylitis tuberculosis. Materials and Methods. Three patients with tuberculous spondylitis in the thoracic, thoracolumbar, or lumbar region with vertebral body collapse of more than 50 percent were included. The patient underwent a 2-stage surgical procedure, consisting of debridement, decompression, and posterior stabilization in the first stage followed by anterior fusion using the lumbotomy approach at the second stage. Twenty million UC-MSCs combined with HA granules in 2 cc of saline were transplanted to fill the vertebral bone defect. Postoperative alkaline phosphatase level, quality of life, and radiological healing were evaluated at one-month, three-month, and six-month follow-up. Results. The initial mean ALP level at one-month follow-up was 48.33±8.50 U/L. This value increased at the three-month follow-up but decreased at the six-month follow-up time, 97±8.19 U/L and 90.33±4.16 U/L, respectively. Bone formation of 50-75% of the defect site with minimal fracture line was found. Increased bone formation comprising 75-100% of the total bone area was reported six months postoperation. A total score of the SF-36 questionnaire showed better progression in all 8 domains during the follow-up with the mean total score at six months of 2912.5±116.67 from all patients. Conclusion. Umbilical cord mesenchymal stem cells combined with hydroxyapatite-based scaffold utilization represent a prospective alternative therapy for bone formation and regeneration of vertebral bone defect due to spondylitis tuberculosis. Further clinical investigations are needed to evaluate this new alternative.